The Impact of Soil Desalination on Reduction of Iron Concentration in Groundwater - Ronny Ronny; Mulyadi Mulyadi (Three E Science Institute, 2020)
Brackish water is one source of clean water and drinking water in coastal areas, river estuaries, and small islands. Various studies have carried out that the use of clay can reduce minerals in the water. This research aims to find out and analyze the Cascade Aerator System and Rapid Sand Filter based on Clay in Reducing Iron Concentration in Well Water. The type of research used is experimental with a quantitative approach. In this study, the researchers used the Pretest-Posttest Control Group Design. The study's location was conducted on Sapuli Island in Pangkep Regency, South Sulawesi Province, and Sindulang Satu Village in Manado City, Central Sulawesi Province. The study's design used a Completely Randomized Design (CRD) with a combination of treatments that obtained 6 x 3 = 18 treatment combinations. This study's population is all well water that is in two research areas, and then the sample collection technique is used simple random sampling with 15 samples of well water. The research obtained a decrease in the maximum average iron (Fe) level obtained reached 57.27% by adding a 20-gram of clay as desalination in 10 liters of well water. The decline that occurred in the two study sites did not differ significantly. Reduction of Iron (Fe) levels through Cascade aerators and Rapid Sand Filters by adding clay as a binder due to the material of kaolin in clay.